Migration and Social Protection in Europe and Beyond (Volume 1) Comparing Access to Welfare Entitlements - Lafleur, Jean-Michel; Vintila, Daniela (IMISCOE Research Series, 2020)
This first open access book in a series of three volumes provides an in-depth analysis of social protection policies that EU Member States make accessible to resident nationals, non-resident nationals and non-national residents. In doing so, it discusses different scenarios in which the interplay between nationality and residence could lead to inequalities of access to welfare. Each chapter maps the eligibility conditions for accessing social benefits, by paying particular attention to the social entitlements that migrants can claim in host countries and/or export from home countries. The book also identifies and compares recent trends of access to welfare entitlements across five policy areas: health care, unemployment, family benefits, pensions, and guaranteed minimum resources. As such this book is a valuable read to researchers, policy makers, government employees and NGO's.